Lambayeque y el norte peruano en un contexto «mundializado» - Aldana Rivera, susana (2006)
At the north of Peru, Lambayeque is a very rich agricultural region that is facing the globalization process as Perú itself. So it is very important to state the region´s historical foundation in order to understand how Lambayeque people –peruvian people– will be related with the global market and also how its agricultural development, its crops and its agricultural products will be realized in such global market.